In vitro activities of U-100592 and U-100766, novel oxazolidinone antibacterial agents. - Zurenko, G E (1996)
Oxazolidinones make up a relatively new class of antimicrobial agents which possess a unique mechanism of bacterial protein synthesis inhibition. U-100592 (S)-N-[[3-[3-fluoro-4-[4-(hydroxyacetyl)-1-piperazinyl]- phenyl]-2-oxo-5-oxazolidinyl]methyl]-acetamide and U-100766 (S)-N-[[3-[3-fluoro-4-(4-morpholinyl)phenyl]- 2-oxo-5-oxazolidinyl]methyl]-acetamide are novel oxazolidinone analogs from a directed chemical modification program. MICs were determined for a variety of bacterial clinical isolates; the respective MICs of U-100592 and U-100766 at which 90% of isolates are inhibited were as follows: methicillin-susceptible Staphylococcus aureus, 4 and 4 micrograms/ml; methicillin-resistant S. aureus, 4 and 4 micrograms/ml; methicillin-susceptible Staphylococcus epidermidis, 2 and 2 micrograms/ml; methicillin-resistant S. epidermidis, 1 and 2 micrograms/ml; Enterococcus faecalis, 2 and 4 micrograms/ml; Enterococcus faecium, 2 and 4 micrograms/ml; Streptococcus pyogenes, 1 and 2 micrograms/ml; Streptococcus pneumoniae, 0.50 and 1 microgram/ml; Corynebacterium spp., 0.50 and 0.50 micrograms/ml; Moraxella catarrhalis, 4 and 4 micrograms/ml; Listeria monocytogenes, 8 and 2 micrograms/ml; and Bacteroides fragilis, 16 and 4 micrograms/ml. Most strains of Mycobacterium tuberculosis and the gram-positive anaerobes were inhibited in the range of 0.50 to 2 micrograms/ml. Enterococcal strains resistant to vancomycin (VanA, VanB, and VanC resistance phenotypes), pneumococcal strains resistant to penicillin, and M. tuberculosis strains resistant to common antitubercular agents (isoniazid, streptomycin, rifampin, ethionamide, and ethambutol) were not cross-resistant to the oxazolidinones. The presence of 10, 20, and 40% pooled human serum did not affect the antibacterial activities of the oxazolidinones. Time-kill studies demonstrated a bacteriostatic effect of the analogs against staphylococci and enterococci but a bactericidal effect against streptococci. The spontaneous mutation frequencies of S. aureus ATCC 29213 were <3.8 x 10(-10) and <8 x 10(-11) for U-100592 and U-100766, respectively. Serial transfer of three staphylococcal and two enterococcal strains on drug gradient plates produced no evidence of rapid resistance development. Thus, these new oxazolidinone analogs demonstrated in vitro antibacterial activities against a variety of clinically important human pathogens.